Comparison of diagnostic performance of RT-qPCR, RT-LAMP and IgM/IgG rapid tests for detection of SARS-CoV-2 among healthcare workers in Brazil - Wilma Patrícia de Oliveira Santos Bernardes; Thais Garcia Santos; Nubia Monteiro Gonçalves Soares Fernandes; Thais Bárbara de Souza Silva; Mateus Westin; Taynãna César Simões; Eduardo Fernandes e Silva; Breno Magalhães Alves; Israel Molina; Mariana de Carvalho Melo; Rubens Lima do Monte-Neto; Rosiane A. da Silva-Pereira; et al. (Elsevier, 2023)
Background: COVID-19 has become a major public health problem after the outbreak caused by SARS-CoV-2 virus. Great efforts to contain COVID-19 transmission have been applied worldwide. In this context, accurate and fast diagnosis is essential. Methods: In this prospective study, we evaluated the clinical performance of three different RNA-based molecular tests - RT-qPCR (Charité protocol), RT-qPCR (CDC (USA) protocol) and RT-LAMP - and one rapid test for detecting anti-SARS-CoV-2 IgM and IgG antibodies. Results: Our results demonstrate that RT-qPCR using the CDC (USA) protocol is the most accurate diagnostic test among those evaluated, while oro-nasopharyngeal swabs are the most appropriate biological sample. RT-LAMP was the RNA-based molecular test with lowest sensitivity while the serological test presented the lowest sensitivity among all evaluated tests, indicating that the latter test is not a good predictor of disease in the first days after symptoms onset. Additionally, we observed higher viral load in individuals who reported more than 3 symptoms at the baseline. Nevertheless, viral load had not impacted the probability of testing positive for SARS-CoV-2. Conclusion: Our data indicates that RT-qPCR using the CDC (USA) protocol in oro-nasopharyngeal swabs samples should be the method of choice to diagnosis COVID-19.